2020
DOI: 10.1038/s41598-020-73915-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrast medium administration with a body surface area protocol in step-and-shoot coronary computed tomography angiography with dual-source scanners

Abstract: We evaluated the feasibility and image quality of prospective electrocardiography (ECG)-triggered coronary computed tomography angiography (CCTA) using a body surface area (BSA) protocol for contrast-medium (CM) administration on both second- and third-generation scanners (Flash and Force CT), without using heart rate control. One-hundred-and-eighty patients with suspected coronary heart disease undergoing CCTA were divided into groups A (BSA protocol for CM on Flash CT), B (body mass index (BMI)-matched patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In 2018, He et al demonstrated a surprisingly lower ED of 2.67 ± 0.98 mSv using a conversion factor of 0.014 mSv/(mGy × cm) but with a 16-cm wide-detector CT [ 13 ]. Compared with He et al’s study with less exposure time of the 16-cm coverage detector [ 13 , 15 ], our study demonstrated that TRO-CTA could be achieved by a dedicated step-and-shoot CCTA that combines the short scan time of high-pitch scan; both of them were widely reported to achieve a lower radiation dose with good image quality [ 16 , 17 , 18 , 19 ], and the step-and-shoot CCTA with AVTS has been adaptive to higher heart rate [ 20 , 21 ]. In addition, the tube voltage at Sn100 of CS reportedly achieves a lower radiation dose without influencing the accuracy of the calcium score [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 63%
“…In 2018, He et al demonstrated a surprisingly lower ED of 2.67 ± 0.98 mSv using a conversion factor of 0.014 mSv/(mGy × cm) but with a 16-cm wide-detector CT [ 13 ]. Compared with He et al’s study with less exposure time of the 16-cm coverage detector [ 13 , 15 ], our study demonstrated that TRO-CTA could be achieved by a dedicated step-and-shoot CCTA that combines the short scan time of high-pitch scan; both of them were widely reported to achieve a lower radiation dose with good image quality [ 16 , 17 , 18 , 19 ], and the step-and-shoot CCTA with AVTS has been adaptive to higher heart rate [ 20 , 21 ]. In addition, the tube voltage at Sn100 of CS reportedly achieves a lower radiation dose without influencing the accuracy of the calcium score [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 63%
“…10,11 Others vary the dose for each patient individually based on physiological parameters such as body surface area. [12][13][14] Similar to these approaches, our CDSS is based on physiological parameters; however, laboratory values and other clinical parameters are also taken into consideration, so that in contrast to the aforementioned works 22 relevant parameters are acquired and used. The result of our system classifies a patient into nonexcessive image contrast/ CM dose (class 1) and excessive image contrast/ CM dose (class 2).…”
Section: Objectivesmentioning
confidence: 99%